2013
DOI: 10.1037/a0032706
|View full text |Cite
|
Sign up to set email alerts
|

College students’ creative attributes as a predictor of cognitive risk tolerance.

Abstract: Previous research has focused on risky decision making rather than calculated risk taking. Cognitive risk tolerance is sensible risk taking based on an individual's ability to formulate and express one's ideas despite potential opposition or negative assessment in regard to reputation, integrity, and honor which we propose is needed for creativity, innovation, and global competitiveness. The goal of this study was to investigate procreative and countercreative attributes and their association with cognitive ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“… Zenasni et al., (2008) show empirically that tolerance for ambiguity interrelates with creativity moderately and positively. Similarly, higher levels of general creativity empirically predict higher levels of cognitive tolerance to risk ( Charyton et al., 2013 ).…”
Section: T Heoretical Frameworkmentioning
confidence: 99%
“… Zenasni et al., (2008) show empirically that tolerance for ambiguity interrelates with creativity moderately and positively. Similarly, higher levels of general creativity empirically predict higher levels of cognitive tolerance to risk ( Charyton et al., 2013 ).…”
Section: T Heoretical Frameworkmentioning
confidence: 99%
“…More recently, Zenasni et al [63] showed empirically that tolerance for ambiguity and creativity are interrelated moderately and positively. Similarly, higher levels of general creativity empirically predict higher levels of cognitive risk tolerance [64]. Furthermore, based on the definitions of creativity, which includes tolerance for uncertainty and constantly seeking innovations as solutions and improvements, we hypothesize that faced with the challenges of climate change [2] or food security [1], creative farmers are more likely to adopt innovative green technologies.…”
Section: Character Strengthsmentioning
confidence: 99%
“…Based on Sternberg and Lubart's (, ) investment theory we speculated that Nobel laureates often are interested in ideas that indicate a less popular idea that then gains popularity and requires greater risk, greater risk tolerance toward opposition and the ability to tolerate uncertainty (Charyton et al., ,b; Kahneman, ,b). We hypothesized that Nobel laureates, being earlier in their careers would need to establish themselves more as well as their ideas.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale is similar to Sternberg and Lubart's (, ) investment theory in that we speculate that Nobel laureates often are interested in ideas that are less popular that then gain popularity. Cognitive skills needed include greater risk tolerance and the ability to overcome opposition as well as tolerate uncertainty (Charyton, Snelbecker, Elliott & Rahman, ,b; Kahneman, ,b).…”
Section: Nobel Laureatesmentioning
confidence: 99%